Characteristic of Nano Zinc Oxide Modified Asphalt Binder and Asphalt Mixture – A Review - Wong, Ken Soon; Khairul Nizam Mohd Yunus, (Recent Trends in Civil Engineering and Built Environment, 2021)
Asphalt mixture is a composite material that is used in road construction. However, the aging of the asphalt mixture has caused the asphalt material to embrittle and stiffer, which would affect the durability of the asphalt mixture and lead to cracking. This study aimed to identify the influence of different amounts of nano-ZnO modified asphalt regarding the aging of asphalt concrete and determine the relationship between nano-ZnO modified asphalt mixture and the aging performance of asphalt mixture. To improve the aging performance of conventional asphalt mixture, a small amount of nano-ZnO is added to the asphalt mixture. This study review the sets of journal article that conducting several experiment with different dosages of nano-ZnO modified asphalt mixture. The samples were tested by penetration test, softening test point test, ductility test and bending rheometer test to determine the physical properties. For rheological characteristics, dynamic shear rheometer test is used to identified. Based on articles, the results can be collected and further analyses can help to find out the most appropriate percentage of nano-ZnO required to be added into original asphalt to produce the most efficient road pavement material.